Determination of Laboratory and Clinical Findings in Patients with Megaloblastic Aanemia - Elkıran, Tamer; Çelebi, Harika (Fırat University, 2001)
Aim: To determine findings of laboratory and clinical in patients with megaloblastic anemia. Matreial and methods: We retrospectively studied hospitalized patients with megaloblastic anemia in Firat University Medical Faculty, the department of Hematology. Physical examination, complete blood counts, morphologic review, reticulocyte count, serum level of vitamin B12 and folic acid, bone marrow aspiration, gastric evaluation and biopsy with endoscopy were done as diagnostic studies. Results: Twenty two patients were evaluated in our study. The mean age was 56±16 (16-95). As clinical finding, we detected glossitis in eight cases, ikter in six cases, oral aphthous lesions in two cases, symptomatic diare in one case.We found vitamin B12 deficiency in fifteen cases, folic acid deficiency in four cases, combined deficiency (both vitamin B12 deficiency and folic acid deficiency ) in three cases. Discussion and conclusion: Vitamin B12 deficiency which is the most common cause of megaloblastic anemia is seen more frequent in older patients. In our study, we found vitamin B12 deficiency as the most common cause of megaloblastic anemia.

Amaç: Megaloblastik anemili hastaların klinik ve laboratuar bulgularını değerlendirmek. Gereç ve Yöntem: Fırat Üniversitesi Tıp Fakültesi Hematoloji servisine yatan megaloblastik anemili hastalar retrospektif olarak incelendi. Hastaların fizik muayenesi, tam kan sayımı, periferik yayma, retikülosit sayısı, serum vitamin B12 ve folik asit seviyeleri, kemik iliği aspirasyonu, endoskopi ile midenin incelemesi ve mide biyopsisi yapıldı. Bulgular: Çalışmaya alınan 22 megaloblastik anemili olgunun yaş ortalaması 56±16 (16-95) yıldı. Klinik bulgu olarak, sekiz olguda glossit, altı olguda sarılık, iki olguda oral aftöz lezyonlar, bir olguda da semptomatik diare vardı. Onbeş olguda vitamin B12, dört olguda folik asit, üç olguda kombine eksiklik (hem folik asit hem de vitamin B12 eksikliği) saptandı. Tartışma ve sonuç: Vitamin B12 eksikliği daha sık yaşlılarda görülmekte olup megaloblastik aneminin en sık nedenidir. Çalışmamızda megaloblastik anemi nedeni olarak en sık vitamin B12 eksikliği saptadık. Vitamin B12 eksikliği yaşlılarda daha fazlaydı.
MEGALOBLASTİK ANEMİLİ HASTALARIN KLİNİK VE LABORATUAR BULGULARININ DEĞERLENDİRİLMESİ